What urban government for a sustainable urban planning? Conceptual analysis based on the case study of Tunisian cities and their local Agenda 21 - Kahloun, Hatem (Environnement Urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2010)
In Tunis, as in most developing cities, the highly centralized system of authority can be seen as the single supplier-regulator of urban development and sustainability. In such contexts in which citizen participation in urban management is undervalued, concepts such as “urban government” and “governance” may appear to be particularly irrelevant to the “networking” practices of actors within their own social and political structures. With a focus on the system of local power in Tunisian cities, this study shows that actions and decisions taken by emerging forms of local government remain highly vulnerable due to extra-local forces. Such a paradox in the forms of power and their manner of conduct, by comparing contextual and conceptual frameworks, draws attention to the issues of democracy in action at the local level and the overall impact of these issues on sustainable urban planning.